Exports, Gender Wage Gaps and Poverty in Honduras - de Hoyos, Rafael E.; Bussolo, Maurizio; Núñez, Oscar (Taylor and Francis, 2013)
This paper identifies and estimates the reduction in poverty attributable to the improved opportunities that international trade integration offered to women in Honduras. The expansion of the export-oriented maquila sector has brought gender equality both in terms of employment and labour earnings. A simulation exercise shows that, at a given point in time, poverty in Honduras would have been 1.5 percentage points higher had the maquila sector not existed. Of this increase in poverty, 0.35 percentage points is attributable to the wage premium paid to maquila workers, 0.1 percentage points to the wage premium received by women in the maquila sector, and 1 percentage point to employment creation.